Hanseníase: Pauci e multibacilares estão sendo diferentes? - Crespo, Maria Júlia Izzo; Gonçalves, Aguinaldo; Padovani, Carlos Roberto [UNESP] (My University, 2014)
Study design: Cross sectional descriptive observational study. Introduction: Present strategy for leprosy control according to World Health Organization is based on respective treatment for pauci or multibacillary patients. Objectives: To compare leper's profiles cared by an university hospital. Materials and Method: Data collected from Leprosy Notification Protocols, Information System for Notifiable Diseases, Celso Pierro Hospital and Maternity, PUC Campinas, years 2007 to 2011. Registers on codified sheets, storage in specific data base and statistical processing by SPSS program. Associations by Goodman's test for contrasts among multinomial populations and by non-parametric Mann-Whitney's, at 5% significance level. Results: 57 new cases have been ascertained, 14 paucibacillary and 43 multibacillary, showing clinical epidemiologic behaviors as expected. Nevertheless, inconsistencies have been observed, as: i) five cases of relapse registered, but not clinically confirmed; ii) a multibacillary case treated as paucibacillary; iii) in relation to forms of detection, similar frequencies of recommendation and spontaneous demand in the multibacillary group; iv) predominance of grade zero disabilities in the paucibacillary group. Conclusions: Results point to the necessity of permanent epidemiological surveillance on leprosy control in order to keep enough dialogue between basic units and reference centers.
Leprosy: Are pauci and multibacillary being diferent?
Keywords: Classification; Health profile; Leprosy; Leprosy, multibacillary; Leprosy, paucibacillary; Leprosy/epidemiology